2015
DOI: 10.1371/journal.pone.0141020
|View full text |Cite
|
Sign up to set email alerts
|

Loss of PTEN Facilitates Rosiglitazone-Mediated Enhancement of Platinum(IV) Complex LA-12-Induced Apoptosis in Colon Cancer Cells

Abstract: We demonstrated for the first time an outstanding ability of rosiglitazone to mediate a profound enhancement of LA-12-induced apoptosis associated with activation of mitochondrial pathway in human colon cancer cells. This effect was preferentially observed in the G1 cell cycle phase, independent on p53 and PPARγ proteins, and accompanied with significant changes of selected Bcl-2 family protein levels. Further stimulation of cooperative synergic cytotoxic action of rosiglitazone and LA-12 was demonstrated in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…We and others previously demonstrated that the cancer cell sensitivity to the cytotoxic effects of LA-12 or cisplatin could be affected by PTEN status [27] , [54] . Importantly, PTEN is known to play a unique role in DNA damage response and cell cycle regulation and can also functionally interact with Chk1 pathway [55] .…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…We and others previously demonstrated that the cancer cell sensitivity to the cytotoxic effects of LA-12 or cisplatin could be affected by PTEN status [27] , [54] . Importantly, PTEN is known to play a unique role in DNA damage response and cell cycle regulation and can also functionally interact with Chk1 pathway [55] .…”
Section: Discussionmentioning
confidence: 91%
“…The cells were harvested, whole cell lysates were prepared and separated by SDS-PAGE, and Western blot analysis was performed as described previously [27] . Immunodetection was carried out using the following primary antibodies: monoclonal mouse anti-p53 (1:1000, #126), monoclonal mouse anti-Chk1(1:1000, #8408), polyclonal rabbit anti-cyclin A (1:1000, #751), monoclonal mouse anti-cyclin B1 (1:1000, #245), monoclonal mouse anti-cyclin D1 (1:1000, #20044), monoclonal mouse anti-PTEN (1:500, #7974), polyclonal rabbit anti-p21 (1:1000, #397), polyclonal rabbit anti-p27 (1:1000, #528) (all from Santa Cruz Biotechnology), polyclonal rabbit anti-phospho-p53 (Ser15) antibody (1:1000, #9284), monoclonal rabbit anti-phospho-Aurora A/B/C (Thr288/232/198) (1:500, #2914), polyclonal rabbit anti-Aurora B (1:500, #3094), polyclonal rabbit anti-phospho-Chk1 (Ser296) (1:500, #2349), monoclonal mouse anti-Chk2 (1:1000, #3440), polyclonal rabbit anti-cleaved caspase-3 (1:500, #9661), polyclonal rabbit anti-cleaved caspase-9 (1:500, #9505), monoclonal rabbit anti-phospho-H2AX (Ser139, γ-H2AX) (1:500, #9718), polyclonal rabbit anti-phospho-histone H3 (Ser10) (1:500, #9701), monoclonal rabbit anti-histone H3 (1:1000, #4499), polyclonal rabbit anti-cleaved PARP (1:1000, #9541), monoclonal rabbit anti-survivin (1:1000, #2808), polyclonal rabbit anti-phospho-Rb (Ser807/811) (1:1000, #9308) (all from Cell Signaling Technology, Danvers, MA), and monoclonal rabbit anti-Cdc25C (1:1000, #1302-1, Epitomics).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The cells were harvested, whole cell lysates were prepared, separated by gel electrophoresis and Western blot analysis was performed as described previously [ 19 ]. Immunodetection was carried out with the following primary antibodies: monoclonal mouse anti-Noxa (1:500, OP180, Calbiochem-MERCK) raised against a recombinant NOXA protein, monoclonal mouse anti-Bcl-2 (1:1000, #509) raised against a synthetic peptide corresponding to amino acids 41–54 of human Bcl-2, polyclonal rabbit anti-poly(ADP-ribose) polymerase (PARP) (1:1000, #7150) against amino acids 764–1014 mapping at the C-terminus of PARP-1 of human origin (both from Santa Cruz Biotechnology), monoclonal mouse anti-caspase-8 (1:1000, #9746) against a synthetic peptide corresponding to the carboxy-terminal sequence of the p18 fragment of human caspase-8, polyclonal rabbit anti-cleaved caspase-3 (1:500, #9661) against a synthetic peptide corresponding to amino-terminal residues adjacent to (Asp175) in human caspase-3, polyclonal rabbit anti-cleaved caspase-9 (1:500, #9505) against a synthetic peptide corresponding to residues surrounding Asp315 of human caspase-9, polyclonal rabbit anti-cleaved PARP (1:1000, #9541) against a synthetic peptide corresponding to carboxy-terminal residues surrounding Asp214 in human PARP, polyclonal rabbit anti-Bak (1:1000, #3792) against a synthetic peptide corresponding to the amino-terminal residues of human Bak, polyclonal rabbit anti-Bid (1:1000, #2002) against a synthetic peptide corresponding to residues surrounding the cleavage site of human BID, monoclonal rabbit anti-Bim (1:1000, #2933) against a synthetic peptide corresponding to residues surrounding Pro25 of Bim, polyclonal rabbit anti-XIAP (1:1000, #2042) against a synthetic peptide corresponding to the amino terminus of human XIAP, polyclonal rabbit anti-Bcl- xL (1:1000, #2762) against a synthetic peptide corresponding to residues surrounding Asp61 of human Bcl- xL , (all from Cell Signaling Technology, Danvers, MA), and monoclonal mouse anti-caspase-10 (1:500, #MO59-3, MBL, Leuven, Belgium) against a recombinant full length human caspase-10.…”
Section: Methodsmentioning
confidence: 99%